2011
DOI: 10.1097/pcc.0b013e31820ac0b3
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide improves systemic microcirculation in infants with hypoxemic respiratory failure

Abstract: Inhaled nitric oxide improves the systemic microcirculation in children with hypoxemic respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
0
26
1
Order By: Relevance
“…In subsequent studies, the family of circulating S-nitrosylated proteins (SNO-proteins) was expanded to include S-nitrosohemoglobin (SNO-Hb), 10 which exhibits the remarkable ability to mediate hypoxic vasodilation, 11 the selective vasodilation in proportion to degree of hypoxemia. A number of recent studies have provided evidence that iNO may utilize SNO-based pathways 12 to confer protection against ischemic insults 8,[13][14][15][16][17][18] -none more remarkable than the report by Terpolilli et al 19 in this issue of Circulation Research, which illustrates beautifully in cerebral vessels the principles of endocrine NO bioactivity and hypoxia-coupled delivery of NO bioactivity. Their demonstration that iNO promotes dilation of cerebral resistance vessels selectively in hypoperfused tissue, without changes in systemic blood pressure, points to new strategies to ameliorate damage after ischemic insult.…”
mentioning
confidence: 68%
“…In subsequent studies, the family of circulating S-nitrosylated proteins (SNO-proteins) was expanded to include S-nitrosohemoglobin (SNO-Hb), 10 which exhibits the remarkable ability to mediate hypoxic vasodilation, 11 the selective vasodilation in proportion to degree of hypoxemia. A number of recent studies have provided evidence that iNO may utilize SNO-based pathways 12 to confer protection against ischemic insults 8,[13][14][15][16][17][18] -none more remarkable than the report by Terpolilli et al 19 in this issue of Circulation Research, which illustrates beautifully in cerebral vessels the principles of endocrine NO bioactivity and hypoxia-coupled delivery of NO bioactivity. Their demonstration that iNO promotes dilation of cerebral resistance vessels selectively in hypoperfused tissue, without changes in systemic blood pressure, points to new strategies to ameliorate damage after ischemic insult.…”
mentioning
confidence: 68%
“…Therefore, measuring microcirculatory blood flow could be regarded as an important addition to the usual macrocirculatory parameters. Microcirculatory parameters have been shown to be able to visualize dysfunctional microcirculation in septic shock in children, effects of inhaled nitric oxide in children with hypoxemic respiratory failure, and in children receiving extracorporeal membrane oxygenation (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…(45) In the only human infant study, patients treated for respiratory failure with inhaled nitric oxide had increased buccal blood flow, confirming its action on peripheral microvasculature. (46) To date, there have been 2 randomized clinical trials in adults of inhaled nitric oxide for the treatment of existing microcirculatory disease. (47) (48) In both adult studies, no difference between the treatment and control arms was reported.…”
Section: Can the Effect Of Hypoxic Vasodilation Be Augmented?mentioning
confidence: 99%